Cosmopolitan cultures of childbirth. Contrasting its anthropological bases from the bioethical perspective - Hernández Garre, José Manuel; De Maya-Sánchez, Baldomero (Acta Bioethica, 2019)
The objective of this article has been to explore, from an ethical perspective, the main anthropological characteristics and bases of childbirth, trying to elucidate, from a personalist position, which patterns are more consistent with respect for maternal dignity and basic principles of bioethics. The methodology chosen was the documentary analysis, through the use of different databases in the field of medical, social and anthropological sciences. The results show bioethically antagonistic approaches, placing, on the one hand, two ontological reductions of a biological nature: medicalized and natural birth, and, on the other, a holistic approach: humanized birth. The first two break with the principle of autonomy and non-maleficiency, as the fate of the mothers is marked by their physiology, a nature that, from a medicalized perspective, is represented from the notions of "risk" and "fragility", leaving the mothers exposed to multiple iatrogenic clinical interventions; while, from the naturist worldview, it is perceived from the notion of "infallibility", which makes them hostages of their supposed anatomical perfection. Ethical conflicts that do not arise in the humanist model, when it represents mothers as global social subjects, who exceed any atomistic reductionism.